Change of collembolan (Hexapoda: Collembola) community structure related to anthropic soil disturbance - Sandler, Rosana V. (2018)
Fil: Sandler, Rosana. Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias; Argentina.